Monetary management of transition in China: Balancing short-run risks and long-run optimality - Markus Diehl; Rainer Schweickert (Kiel Institute for World Economics (IfW), 2005)
Expecting an appreciation of the Chinese currency seems to be a safe bet. There is a mounting pressure from U.S. representatives, and a majority of economists seem to believe that the Chinese economy is overheating and that the dollar peg should be loosened as soon as possible. Indeed, a nominal appreciation may help reduce reserve inflows and allow for a more autonomous monetary policy in the case of overheating. A plausible strategy would be a small one-step revaluation, which would bring the renminbi to parity with the Hong Kong dollar. However, such an adjustment may provoke additional speculative capital inflows and is not even necessary to bring about the real appreciation. Overheating should lead to an increase in domestic inflation rates above the U.S. level, which – given the fixed nominal exchange rate – delivers the real appreciation. There are certain signs that the Chinese economy is not characterized by overheating but rather by overinvestment. Indications for overinvestment are the strong expansion of investment above 40 percent of GDP, the increase in real estate prices in high-growth regions, and the lack of a strong increase in consumer prices. In that case, the present restrictive policy mix of the Chinese authorities is preserving the situation of excess supply and undervaluation. A nominal appreciation would even increase the internal imbalance, as claimed by Chinese authorities. Whereas the diagnosis is controversial with respect to overheating versus overinvestment, undervaluation can be taken as a stylized fact. Hence, short-run adjustment could be achieved by less restrictive monetary and fiscal policies conditional on the development of the consumer price inflation which should be allowed to show a positive differential versus the U.S. consumer price inflation. Apart from such short-run consideration, the more general question is how to sequence the shift to a flexible exchange rate regime, which seems to be adequate for a large country like China. On the one hand, it is plausible that China should learn to float while the capital account is relatively closed. On the other hand, both opening up the capital account and introducing exchange rate flexibility need a certain degree of capital market development. Additionally, one-side bets on the direction of exchange rate movements when giving up a peg should be avoided. Both preconditions are currently not given in the case of China. The priorities for balancing short-run adjustment and long-run optimality are (1) a real appreciation via higher consumer price inflation and (2) speeding up domestic capital market reform as long as capital controls are effective to some extent. This should allow phasing in an augmented inflation targeting regime and avoiding a hard landing, which otherwise may be the consequence of lifting a solid exchange rate anchor in stormy waters.
Keywords: 330; Geldpolitik; Währungspolitik; Aufwertung; Kapitalmarktliberalisierung; Kapitalverkehrspolitik; Flexibler Wechselkurs; China